Experimental investigation of unconfined spherical and cylindrical flame propagation in hydrogen-air mixtures. (31st March 2021) - Grune, J.; Sempert, K.; Kuznetsov, M.; Jordan, T.
Abstract: This paper presents results of experimental investigations on spherical and cylindrical flame propagation in pre-mixed H2 /air-mixtures in unconfined and semi-confined geometries. The experiments were performed in a facility consisting of two transparent solid walls with 1 m 2 area and four weak side walls made from thin plastic film. The gap size between the solid walls was varied stepwise from thin layer geometry (6 mm) to cube geometry (1 m). A wide range of H2 /air-mixtures with volumetric hydrogen concentrations from 10% to 45% H2 was ignited between the transparent solid walls. The propagating flame front and its structure was observed with a large scale high speed shadow system. Results of spherical and cylindrical flame propagation up to a radius of 0.5 m were analyzed. The presented spherical burning velocity model is used to discuss the self-acceleration phenomena in unconfined and unobstructed pre-mixed H2 /air flames. Highlights: We study spherical and cylindrical H2 /air flames in un- and semi-confined geometries. A large-scale shadowgraphy for high-speed applications used to measure visible flame. Mixture specific flame acceleration observed for spherical flame propagation. A spherical burning velocity S(sph) for undisturbed flame propagation was derived. The model is in agreement with experimental data for spherical flame propagation.